Study on the Insulation Resistance Detection Technique of Photovoltaic Power Generation Facilities - Lee, Ki-Yeon; Kim, Dong-Woo; Lim, Young-Bae; Kwon, Soon-Young; Ryu, In-Ho (International Journal of Engineering and Technology, 2018)
Background/Objectives:This paper explains the insulation resistance detection technology to secure electrical safety as there is possibility of electricity disaster in the case of insulation failure in DC power line of photovoltaic power generation facilities.Methods/Statistical analysis:An algorithm was developed to measure and calculate insulation performance of each power line by using an asymmetric high resistance circuit for voltage size generated in a live condition. It calculates total insulation resistance including DC power facilities by using an asymmetric voltage measurement circuit, and then insulation resistance of each (+)/(-) power line by using a symmetric voltage measurement circuit. A failure location can be assumed based on the ratio of calculated insulation between (+) and (-) power lines.Findings:In the case of DC power facilities, realtime monitoring of insulation condition is not possible as leakage current cannot be measured by using ZCT. Currently, the megger is used for measurement in a power-off condition. However, test in a live condition can detect photovoltaic panel failure or insulation condition of power lines. In this paper, we developed an algorithm for insulation performance by using an asymmetric high resistance detection circuit as well as technology to detect failure location of string based on the characteristics of photovoltaic power facilities. Accordingly, we suggested methods to secure electrical safety with realtime monitoring of DC power facilities and testing equipment.Improvements/Applications:The future development of insulation monitoring equipment in a live condition and state diagnosis device using the DC power line insulation performance algorithm will contribute to electrical safety of DC power facilities.Â